Impact of Cloud-Based Accounting Information Systems on Decision-Making Quality - Kristiyanthi, Anak Agung Dwi; Sujana, I Ketut; Wirama, Dewa Gede; Ratnadi, Ni Made Dwi (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 2 (2024)DO - 10.24843/JIAB.2024.v19.i02.p09, 2024)
This study investigates the factors influencing the adoption of cloud-based Accounting Information Systems (AIS), extending the Unified Theory of Acceptance and Use of Technology (UTAUT) to include new critical factors pertinent to decision-making processes. Employing a quantitative methodology, the research tested hypotheses through questionnaires, which served as the primary instrument for data collection. Data analysis was conducted using structural equation modeling with Smart PLS. The findings indicate that performance expectancy and the utilization of artificial intelligence significantly impact the intention to use cloud-based AIS. Moreover, both the intention to use and the presence of facilitating conditions positively affect actual usage behavior. It was also determined that actual usage behavior has a favorable impact on the quality of decision-making. This research underscores the importance of technology acceptance factors in influencing the effective implementation and utilization of cloud-based AIS, thereby enhancing decision-making quality within organizations. Keywords: UTAUT extensions, cloud-based accounting, use of artificial intelligence, decision-making quality